Narrative Review: The Intersection of Genetic Predisposition for Autism Spectrum Disorder and Nurture Factors in the Development of Borderline Personality Disorder - Fatima, Zarmeen; Asad, Noor (International Journal of Psychology, 2025)
Purpose: This narrative review explores the significant overlaps between Borderline Personality Disorder (BPD) and Autism Spectrum Disorder (ASD), focusing on shared symptoms and genetic underpinnings. The purpose was to investigate neurodivergent traits in BPD similar to autism and examine how genetic predisposition for ASD can increase BPD risk when faced with adverse childhood experiences. Despite different DSM-5 classifications, both disorders share traits like emotional dysregulation, interpersonal difficulties, and cognitive distortions. Genetic markers, including variations in BDNF, COMT, and CNTNAP2 genes, suggest a shared biological vulnerability. The review posits that a family history of ASD may increase BPD likelihood during adolescence, especially when encountering adverse childhood experiences (ACEs). This interplay between genetic predisposition and environmental stressors highlights the need for improved BPD diagnostic criteria and tailored interventions. Methodology: A comprehensive literature search was conducted using databases such as PubMed, Semantic Scholar, and Google Scholar. Key search terms included "Autism Spectrum Disorder," "Borderline Personality Disorder," "Genetic Overlap," and "Theory of Mind." The review focused on peer-reviewed studies from the last decade, with some foundational papers included for historical context. Findings: The review uncovered notable overlaps between ASD and BPD in genetics, neurocognition, and symptomatology. Shared genetic factors include variations in the BDNF, COMT, SHANK3, and CNTNAP2 genes. Neurocognitive similarities were evident in impairments like social cognition, emotional regulation, and facial expression processing. Overlapping symptoms such as emotional dysregulation, Theory of Mind deficits, and executive dysfunction emphasize the neurodivergent nature of BPD. Importantly, the review suggests that a family history of ASD, combined with exposure to adverse childhood experiences (ACEs), may increase the risk of developing BPD during adolescence. Unique Contribution to Theory, Practice and Policy: This review reimagines BPD within a neurodivergent framework, similar to ASD, focusing on its neurobiological foundations. It supports an integrated theoretical model highlighting the neurodivergent traits of BPD which are similar to those of ASD. In clinical practice, the review emphasizes the importance of recognizing overlaps during assessment to improve diagnostic accuracy and inform tailored interventions. It advocates for incorporating neurodiversity-affirming practices into BPD treatment, inspired by approaches used in ASD care. The findings encourage deeper study of the shared genetic and neurodevelopmental aspects of BPD, potentially leading to improved treatment and diagnostic models.